Ascent to “Natural Humanness”: Immanuel Kant in the Philosophical Anthropology of Gustav Shpet - Tatiana G. Shchedrina; Boris I. Pruzhinin (Кантовский сборник)
The archive of Gustav Shpet contains scattered preparatory materials for his works. Some of these handwritten rough drafts are devoted to Immanuel Kant. These jottings enable us to take a new look at possible trajectories of philosophical anthropology. The main goal of this article is to show, on the one hand, the modern relevance of Kant’s reflections on the essence of the human being and, on the other hand, the productiveness of their critical reinterpretation by Shpet. In effect, Kant’s reflections give us an insight into the sources of the current anthropological crisis when “the free man”, capable of creating himself, has finally detached himself from his nature (i.e. accomplished what Kant believed to be the foundation of anthropology). Shpet’s critique enables us to outline the contours of a positive way out of today’s critical situation. To implement this task, the authors carry out a historical-philosophical analysis of Shpet’s treatment of the question of philosophical anthropology. This is a new approach both for Shpet scholarship and for the Russian philosophical tradition, an approach that opens up a new path to overcome the crisis and, what is more, a path that is ecologically significant. This gives us all the more reason to try to find the critical points of anthropologism (easy enough if we turn to Shpet’s article “The Anthropologism of Lavrov in Light of the History of Philosophy”). It also encourages us to reinterpret in an anthropological context Shpet’s reflections on the human being and humanness (see the article “Wisdom or Reason?”). The Supplement contains the first ever publication of a historical document, a letter Shpet received from the German embassy in 1924, inviting him to Königsberg for the celebration of the 200th anniversary of Kant’s birth and a programm of the event with the names of speakers and the topics of their presentations.